BUSINESS PROCESS MODEL AND NOTATION (BPMN) DESIGN FOR A BARCODE SCANNER-BASED SALES INFORMATION SYSTEM AT THE COOPERATIVE OF THE ACCOUNTING DEPARTMENT, STATE POLYTECHNIC OF MALANG - Gracesheila Florencia Tumbelaka; Aang Afandi; Kartika DS Susilowati (ZILLZELL MEDIA PRIMA, 2025)
This study aims to design a Business Process Model and Notation (BPMN)-based sales information system integrated with barcode scanner technology at the Cooperative of the Accounting Department, State Polytechnic of Malang. The system is developed to address inefficiencies and weaknesses in sales report control, such as the absence of real-time monitoring, lack of structured authorization, and reliance on manual documentation. A qualitative case study method was employed, involving direct observation and interviews with cooperative staff and department administrators. Data were analyzed and modeled using BPMN to visualize both current (as-is) and redesigned (to-be) business processes. The proposed system introduces features such as automated transaction recording, role-based access, and a three-layer validation process. Reports are only accessible or printable upon authorization by the Head of Department, ensuring better financial transparency and data integrity. The result is a more accountable, efficient, and user-oriented cooperative management system.